E-mail reminders improve completion rates of patient-reported outcome measures - Triplet, Jacob J. (JSES Open Access, 2017)
BACKGROUND: Patient-reported outcome measures (PROMs) have become increasingly important in assessing clinical outcomes. However, acquisition of data at routine time intervals can be challenging. The ability of e-mail reminders to save follow-up intervals when office visits are missed is unknown. MATERIALS AND METHODS: A retrospective review of a consecutive series of 186 shoulder surgical patients who underwent surgery between October 2, 2012, and July 2, 2013, was conducted. Simple Shoulder Test and 12-Item Short Form Health Survey scores were completed at preoperative visits using office-based tablet surveys. Patients were observed for completeness of PROMs at expected routine follow-up of 1 year and 2 years. When office visits were missed, e-mail reminders with links to online surveys were sent to patients without further incentives. Improvement in data acquisition achieved using e-mail reminders when patient follow-up was missed was assessed. The influence of the procedure performed was further analyzed to determine whether patients treated with different surgical procedures would be more compliant with PROM completion. RESULTS: Use of e-mail reminders significantly increased the number of patients for whom complete follow-up data were obtained. Compared with tablet surveys completed during office visits alone, the addition of e-mail reminders increased the collection of complete PROM data (both 1- and 2-year follow-up) by 25.8% (P < .001). Similar findings were observed for total shoulder arthroplasty and arthroscopic rotator cuff repair patients (increased by 25.7% and 34.4%, respectively; P < .001). CONCLUSION: E-mail reminders serve as a mechanism to increase the completeness of follow-up data in the absence of in-office patient evaluation.